Pengaruh Electronic Word of Mouth Twitter dan Brand Image Terhadap Minat Beli Produk Avoskin (Survei Pada Followers Akun Twitter @avoskinbeauty) - Rizki Amelia; Salim Siregar (Peneliti.net, 2022)
This study aims to determine, explain, and analyze the effect of Electronic Word of Mouth and Brand Image on buying interest of Avoskin products on followers of the Twitter account @avoskinbeauty. This research uses descriptive and verification methods. The sample in ths study was 400 respondents using accidental sampling. The data analysis with the help of Microsoft Excel 2016 and SPSS version 21. The result of this study indicate that there is a significant partial effect of electronic word of mouth by 15,4% and bran image by 56,1% on interest buying Avoskin products. There is a significant simultaneous effect of electronic word of mouth and brand image on interest buying Avoskin product by 71,5% and 28,5% influenced by other variables not examined.